2011
DOI: 10.1536/ihj.52.224
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Plasma Homocysteine Levels and Congestive Heart Failure in Patients With Acute Myocardial Infarction Homocysteine and Congestive Heart Failure

Abstract: SummaryHeart failure after acute myocardial infarction (AMI) is an important factor in determining clinical outcome. We examined whether the plasma homocysteine level was a predictor of heart failure in patients with AMI. A series of 96 patients without renal failure who were admitted to our hospital because of AMI between January 2003 and December 2005 were assigned to two groups; a group with a high homocysteine level (group H: n = 48) and a group with a low homocysteine level (group L: n = 48) based on a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 35 publications
(57 reference statements)
1
9
0
5
Order By: Relevance
“…Consistent with previous reports (8,1924), our data demonstrated that in the adverse events group the ages of the patients were higher than those in the control group and the proportion of females was significantly higher than that in the control group. The morbidity of hypertension in the adverse events group was higher than that in the control group and UA, HCY and CK levels, as well as CKMB enzyme peak were clearly higher than those in the control group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous reports (8,1924), our data demonstrated that in the adverse events group the ages of the patients were higher than those in the control group and the proportion of females was significantly higher than that in the control group. The morbidity of hypertension in the adverse events group was higher than that in the control group and UA, HCY and CK levels, as well as CKMB enzyme peak were clearly higher than those in the control group.…”
Section: Discussionsupporting
confidence: 93%
“…A study has shown that with increasing age, the morbidities of hypertension and old myocardial infarction in AMI patients are significantly increased and the incidence rates of mechanical complications, arrhythmia and multivessel disease are also clearly higher than in younger patients (1,2). The hospital mortality rate of female AMI patients is significantly higher than that of males (3,4) and the increase of serum uric acid (UA) (57) and homocysteine (HCY) (8) increases the morbidity and mortality of cardiovascular diseases. Age, gender, blood pressure, lipid level and blood glucose are predictors influencing the outcome of AMI.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple small clinical studies have demonstrated that blood homocysteine levels are elevated in patients with heart failure compared to control population [81,82,83,84]. Blood homocysteine level is also related to the clinical severity of heart failure [85].…”
Section: Methionine-homocysteine Cycle Folate Metabolism and Heamentioning
confidence: 99%
“…Furthermore, left ventricular diastolic function is significantly worse in hypertensive patients with elevated levels of homocysteine compared to hypertensive patients with normal homocysteine levels [3]. Finally, plasma homocysteine levels predict heart failure incidence in patients with or without prior myocardial infarction [4][5][6].…”
Section: Introductionmentioning
confidence: 99%